Sex Therapy in a Cultural Context - Štulhofer, Aleksandar (Array, 2009)
The paper comments on the article (Mean & Binik, 2009) which proposed the abolition seksaualne therapy as a specialized psychotherapeutic branches and advocates for its incorporation into multidiciplinarno field of sexology. The paper's authors believe this proposal problematic, especially in the cultural context in which they operate.